Extended subject – matter under intellectual property law: The paradigm of copyright, trademarks and patents regarding Computer Icons and Graphical User Interfaces - Lefakis, Leandros (Journal of Integrated Information Management, 2024)
Purpose – Intellectual property law has developed legal rules that carefully balance competing interests. It is a fact that the main goal has long been to provide legal protection to maximize incentives to engage in creative and innovative activities, while also providing rules and doctrines that minimize the effect on the commercial marketplace and diminish interference with the free flow of ideas in general. This article examines the extension of the subject - matter that can be protected under intellectual property law. The extensive view of protectable subject - matter via intellectual property has blurred the clear delineation between patent, copyright, and trademark law. This has led to overlapping protection which allows multiple means to protect the same subject - matter. Such protection is problematic because it interferes with the carefully developed doctrines that have evolved over time to balance the private property rights against public access to creations protected by intellectual property. Approach and Originality/value - This article discusses a new topic concerning the extension domain of subject - matter protected by patents, trademarks and copyright law regarding computer icons and graphical user interface. Furthermore, it examines the overlaps that exist and the resulting problems regarding these specific areas of intellectual property law. Findings - The extension of the subject - matter protected under patent, copyright, or trademark law should only occur if it does not subvert the balance of intellectual property law per se. The reason is that uncareful expansion could cause unintended over-protection of the rights of creators and innovators in contrast to the public interest. The paradigm of CIs and GUIs fits perfectly with the view expressed above.